Artistic Interpretation of Universal Ideas in Alisher Navoi's Work "Arba'in" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
in this article, personal education and aspects that should be paid attention to, the importance of science and its place in society and human life, features that should not be formed in a person's character; comments are made about their reflection in the content of the continents in "Arba'in".